The nature of workplace communication - Swann, David; Collins, Cath; Boland, Michael; Video Education Australasia (Victoria, AU : Video Education Australasia, 2007)
This program is about communicating in the workplace and follows a week in the life of fictional cleaning company Clean as Krystal. With manager Barry Walton as your guide, this program covers topic such as what is communication, barriers to effective communication, communication at work and effective workplace communication skills. The mockumentary style program will assist the student to apply the communication theory to the workplace. It becomes clear that what is often regarded as the simplest work skill, communication is quite complex and can go wrong at many points of the process
Title from container
Executive producer : Mark McAuliffe ; senior producer : Richard Leigh ; editor : Paul Sutherland ; camera : Peter Zakharov
Voice over : Michael Szuc
Keywords: Communication in personnel management; Communication in management; Communication in organizations; Interpersonal communication; Business communication